2008
DOI: 10.1177/1368430208090647
|View full text |Cite
|
Sign up to set email alerts
|

Leader—Follower Effects in Resource Dilemmas: The Roles of Leadership Selection and Social Responsibility

Abstract: Previous research on the allocation of scarce resources shows that when people are assigned labels of leader or follower in their group, leaders allocate more of the scarce resources to themselves than followers do. In three laboratory studies, we examine the idea that how people are selected for the leader role (i.e. election or appointment) determines whether leaders take more or equal shares (relative to followers) from a common resource. In a first experiment, we show that participants were more accepting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 40 publications
(58 reference statements)
1
45
0
Order By: Relevance
“…First, past work that has compared appointed to elected leader systems has consistently shown that electing leaders enhances public good production after the leader is installed (Baldassarri and Grossman 2011;De Cremer and Van Dijk 2008;Grossman and Baldassarri 2012). But second, I consider an additional mechanism by which leader election (vs. appointment) can promote public good production-by allowing group members to compete for leadership before the election takes place.…”
Section: Hypothesis 6: Given the Ability To Elect Their Leaders Peopmentioning
confidence: 98%
“…First, past work that has compared appointed to elected leader systems has consistently shown that electing leaders enhances public good production after the leader is installed (Baldassarri and Grossman 2011;De Cremer and Van Dijk 2008;Grossman and Baldassarri 2012). But second, I consider an additional mechanism by which leader election (vs. appointment) can promote public good production-by allowing group members to compete for leadership before the election takes place.…”
Section: Hypothesis 6: Given the Ability To Elect Their Leaders Peopmentioning
confidence: 98%
“…as being assigned to the role by a higher authority) acted more in line with self-interests. While these results also point to the relevance of selection procedures, they especially show that even such small changes in the labelling of power affect how power is understood and exercised (De Cremer and van Dijk 2008). This finding indicates that if a power holder actually receives his or her position via election by the subordinates (rather than, for example, by excelling in the job interview or internal promotion), including the label 'elected' -for example, on the business card -may constitute a fruitful first step to promote responsible leadership.…”
Section: How the Social Context Shapes The Construal And Exercise Of mentioning
confidence: 84%
“…While previous findings indicate that construing power as responsibility (versus opportunity) is likely to facilitate responsible action towards others among power holders (e.g. Chen et al 2001, De Cremer and van Dijk 2008, Overbeck and Park 2006, the consequences for communication are less clear. Power construed as responsibility implies that an individual focuses on social concerns, such as being sensitive to others' feelings and sharing important resources.…”
Section: Construing Power As Responsibility Versus Opportunity: Implimentioning
confidence: 86%
See 2 more Smart Citations